1978
DOI: 10.2135/cropsci1978.0011183x001800020017x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability in Post‐harvest Respiration Rates of Sugarbeet Roots1

Abstract: Post‐harvest respiration rates were measured on whole sugarbeet (Beta vulgaris L.) roots from 97 inbred and hybrid breeding lines to determine the magnitude of the genetic variability. Measurements were made between 50 and 160 days of storage at 5 C on 19 hybrids and inbreds grown at two locations; on eight hybrids and inbreds in 2 successive years; and on 76 inbreds.A high correlation (r=0.90**) existed between the loss of sucrose and respiration rate. The respiration rate of the entries varied between years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Many sugar beet storage studies involve measurement of respiration in vitro (Cole 1977;Wyse et al 1978;Wyse and Peterson 1979). Recent work has suggested that respiration is influenced more by environment and environment by genotype interactions than genotype alone (Campbell and Klotz 2007).…”
Section: Cultivar Effect On Sugar Beet Storagementioning
confidence: 99%
“…Many sugar beet storage studies involve measurement of respiration in vitro (Cole 1977;Wyse et al 1978;Wyse and Peterson 1979). Recent work has suggested that respiration is influenced more by environment and environment by genotype interactions than genotype alone (Campbell and Klotz 2007).…”
Section: Cultivar Effect On Sugar Beet Storagementioning
confidence: 99%
“…Respiration Respiration rate is highly and predictably correlated with sucrose loss (Wyse, Theurer & Doney, 1978), since sucrose is the main storage carbohydrate in sugar beet and the most important carbohydrate source for respiratory activity. Respiration accounts for 70-80% of sucrose loss during storage (Koster, Raats & Jorritsma, 1980).…”
Section: Physiology Biochemistry and Cell Biology Of Bruisingmentioning
confidence: 99%
“…Ex Fr., and Penicillium claviforme Brainier) have been developed and released to the public (Bugbee 1978;Campbell and Bugbee 1985). Differences in storage respiration rates among sugarbeet lines and hybrids have been acknowledged for some time (Nelson and Wood 1950;Cole 1977) and it appears there is sufficient genetic diversity for development of genotypes with low respiration rates in storage (Wyse et al 1978). The invert sugars, glucose and fructose, produced by the breakdown of sucrose, not only represent a direct loss of sucrose, but also hinder processing efficiency and decrease sucrose extractability (Dutton and Huijbregts 2006).…”
mentioning
confidence: 99%